Orthokeratology with increased compression factor (OKIC): study design and preliminary results. Issue 1 (4th May 2020) - Wan, Kin; Lau, Jason Ki-kit; Cheung, Sin Wan; Cho, Pauline
Abstract : Objective: To present the study design and the baseline data of a prospective cohort study investigating the safety, refractive correction and effectiveness of myopia control in subjects fitted with orthokeratology (ortho-k) lenses of different compression factors. Methods and analysis: This study is a 2-year longitudinal, double-masked, partially randomised study. Myopic children aged between 6 and 10 years are recruited and they may choose to participate in either the ortho-k or spectacle-wearing group. Subjects in the ortho-k group are randomly assigned to wear ortho-k lenses of either conventional compression factor (CCF, 0.75 D) or increased compression factor (ICF, 1.75 D). For the ortho-k subjects, the time and between-group effects within the first month of lens wear were analysed. Results: Sixty-nine ortho-k subjects (CCF: 34; ICF: 35) and 30 control subjects were recruited. There were no significant differences in baseline demographic data among the three groups of subjects (p>0.19). At the 1-month visit, the first fit success rates were 97% and 100% in the CCF and ICF ortho-k group, respectively. A higher percentage of ICF subjects could achieve full correction (CCF: 88.2%; ICF: 94.3%). The change in axial length was significantly higher in the ICF group (CCF, 0.003 mm; ICF, −0.031 mm) (p<0.05). No significant between-group differences in daytime vision or in the coverage and depth of corneal staining between the two ortho-k groups (p>0.05) were observed at any visit. Conclusion: ICF did not compromise the corneal integrity and the lens centration within the first month of lens wear. The preliminary performance of ortho-k lenses with ICF of 1.00D shows that it was safe to be used in the longer term for the investigation of myopia control. Trial registration number: NCT02643342 .